Microbial contamination of bedding material: one health in poultry production - Gomes, Bianca (2022)
In poultry farms, the mixture of bedding material, chicken excrement, and feathers seems to play an important role in pathogen development which may contribute to a potential risk of zoonosis, spreading the disease through the food chain. The purpose of this study was to analyze microbial contamination in bedding material and other matrices as well as potential antimicrobial resistances in chicken production facilities and also to identify the sampling techniques and assays used. This study evidences the available data published, following the PRISMA methodology. Among the environmental samples, surface swabs were frequently used as a passive sampling technique. Morphological identification was performed in all studies. Of all the matrices, the bedding material was the most contaminated. Most studies focused on bacterial contamination, with Salmonella sp. and Campylobacter sp. being commonly reported and three studies evidenced fungal contamination, being Penicillium sp.- and Aspergillus sp.-dominant. Mycotoxin assessment was only performed in one study, being identified in all bedding samples. The screening for bacteria resistance evidenced bacteria multidrug resistance; however, fungal susceptibility to azoles was not assessed in any of the analyzed studies. Briefly, this review evidences microbial contamination in poultry facilities, emphasizing animals’ bedding as a potential source of contamination. Additionally, this study contributes to a sampling and analysis protocol proposal to assess microbial contamination in this setting. Additionally, the knowledge gaps identified highlight the need for further research regarding microbial contamination and toxicological potential on animals’ bedding in order to mitigate exposure in poultry pavilions.